Does patient history and physical examination predict MRI proven cauda equina syndrome? - Fairbank, Jeremy; Hashimoto, Robin; Dailey, Andrew; Patel, Alpesh A; Dettori, Joseph R (Evidence-Based Spine-Care Journal, 2011)
Study design: Systematic review.Study rationale: While magnetic resonance imaging (MRI) is used as the diagnostic gold standard for cauda equina syndrome (CES), many MRI scans obtained from patients presenting with signs and/or symptoms of CES do not reveal concordant pathology. As a result, the role of the history and physical examination remains unclear when determining which patients require emergent MRI. Objective or clinical question: Are there elements from the history or physical examination that are associated with CES as established by MRI?Methods: A systematic review of the literature was undertaken for articles published through April 13, 2011. PubMed, Cochrane, National Guideline Clearinghouse Databases, and bibliographies of key articles were searched. Two independent reviewers reviewed articles. Inclusion and exclusion criteria were set and each article was subject to a predefined quality-rating scheme.Results: We identified four articles meeting our inclusion criteria. All studies evaluated patients with symptoms suggestive of CES and compared symptoms and/or signs with findings at MRI. The mean prevalence of CES as diagnosed by MRI ranged from 14%–48% of patients. No symptoms or signs reported by more than one study showed high sensitivity and specificity, and all likelihood ratios were low. Symptoms included back/low back pain, bilateral sciatica, bladder retention, bladder incontinence, frequent urination, decreased urinary sensation, and bowel incontinence; signs included saddle numbness and reduced anal tone.Conclusions: There is low evidence that individual symptoms or signs from the patient history or clinical examination, respectively, can be used to diagnose CES. Additional prospective studies are needed to evaluate whether any single and/or combination of symptoms are associated with a positive diagnosis of CES.